Analytical solutions of Phi-four equation - Demiray, Şeyma Tülüce; Bulut, Hasan (My University, 2017)
This study bases attention on new analytical solutions of Phi-four equation. Themodified exp??? ?? ?? -expansion function method (MEFM) has been used toobtain analytical solutions of the Phi-four equation. By using this method, darksoliton solutions and trigonometric function solution of the Phi-four equationhave been found.
Keywords: Fizik; Uygulamalı; Matematik